1989
DOI: 10.1002/ar.1092230406
|View full text |Cite
|
Sign up to set email alerts
|

S‐100 protein‐immunoreactive cells in the bovine ovary

Abstract: The present study deals with an immunohistochemical localization of S-100 protein in the bovine ovary. Immunoreactivity for S-100 was observed in various types of cells, as well as in cells of the nervous system. The endothelial cells of arterial vessels, blood capillaries, and lymph vessels; the epithelial cells of ovarian cysts; and the oocytes of normal and atretic follicles showed an S-100 protein positivity. The immunoreactivity also was found in the epithelial cells of the rete ovarii. No cells other tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Small S100-positive blood vessels penetrate the dispersed granulosa cells. Immunoreactivity for S100 protein was also observed in the ovarian rete as well as in ovarian cysts [Kamiya et al, 1989]. Haimoto et al [1987] describe S100 expression in the oocytes of primordial follicles and in their follicle epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Small S100-positive blood vessels penetrate the dispersed granulosa cells. Immunoreactivity for S100 protein was also observed in the ovarian rete as well as in ovarian cysts [Kamiya et al, 1989]. Haimoto et al [1987] describe S100 expression in the oocytes of primordial follicles and in their follicle epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, S-100 proteins were considered to be specific for nervous tissue [Bock, 1978]. However, numerous immunohistochemical and biochemical studies have revealed that S-100 proteins are also present in other tissues than the nervous system, particularly in the ovary [Kamiya et al, 1989], bovine testis [Ahmed and Sinowatz, 2005], and bovine ovary [AbdElhafeez et al, 2011]. S-100 proteins belong to a family of Ca 2+ -binding proteins [Isobe et al, 1982] and display different cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…1986: Iwanaga et al, 1987: Sugimura ct al.. 1987Kamiya et al. 1989], Despite many reports of S-100 pro tein in the intra-and extraneural tissues, little is known about the function of S-100 [Zimmer and Van Eldik, 1987], The present study is the first to demonstrate the locali zation of S-100 protein in the bovine oviduct.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, immunohistochemical and immunochemical studies have revealed that S-100 protein is not specific for nervous tissues but is widely dis tributed among animal and human cells such as chondro cytes, adipocytes, macrophages, follicular dendritic cells andoocytes [Takahashietal.. 1984;V anstapeletal.. 1986: Iwanaga et al. 1987: Sugimura et al, 1987Uchida and Endo, 1988;Kamiya et al. 1989].…”
Section: Introductionmentioning
confidence: 99%